Correlation between Thyroid-related Hormones and Preeclampsia - Al-Naqeeb, Asmehan (Iraqi National Journal of Nursing Specialties, 2010)
Objectives: In order to highlight the TSH and thyroid hormones levels in preeclamptic and healthy pregnant women. Methodology: Ninety patients with preeclampsia were divided into two groups according to the severity of disease; those with mild disease (37 patients) and those with a severe form (53 patients). A separate group of 30 normal women were included as a normal control group. Venus blood samples were collected from all groups and the serum was obtained for hormone analysis by ELISA test. Results are expressed using SPSS for window version 11.0. Results: Mean serum TSH levels were significantly increased in both of mild and severe preeclampsia compared with normal pregnancy, and T3 serum level showed a significant increase in mild and severe preeclamptic women compared with healthy pregnant ones without concomitant change in T4 in each group of preeclamptic women compared to normal pregnancy. Recommendations: Studying the relationship between preeclampsia and its effect on the secretion of pituitary gland to ADH, studying the role of adrenal gland, hypothalamus and their secretions in preeclampsia.